CDK Family PROTAC Profiling Reveals Distinct Kinetic Responses and Cell Cycle–Dependent Degradation of CDK2. (April 2021) - Riching, Kristin M.; Schwinn, Marie K.; Vasta, James D.; Robers, Matthew B.; Machleidt, Thomas; Urh, Marjeta; Daniels, Danette L.
Targeted protein degradation using heterobifunctional proteolysis-targeting chimera (PROTAC) compounds, which recruit E3 ligase machinery to a target protein, is increasingly becoming an attractive pharmacologic strategy. PROTAC compounds are often developed from existing inhibitors, and assessing selectivity is critical for understanding on-target and off-target degradation. We present here an in-depth kinetic degradation study of the pan-kinase PROTAC, TL12-186, applied to 16 members of the cyclin-dependent kinase (CDK) family. Each CDK family member was endogenously tagged with the 11-amino-acid HiBiT peptide, allowing for live cell luminescent monitoring of degradation. Using this approach, we found striking differences and patterns in kinetic degradation rates, potencies, and Dmax values across the CDK family members. Analysis of the responses revealed that most of the CDKs showed rapid and near complete degradation, yet all cell cycle–associated CDKs (1, 2, 4, and 6) showed multimodal and partial degradation. Further mechanistic investigation of the key cell cycle protein CDK2 was performed and revealed CDK2 PROTAC-dependent degradation in unsynchronized or G1-arrested cells but minimal loss in S or G2/M arrest. The ability of CDK2 to form the PROTAC-mediated ternary complex with CRBN in only G1-arrested cells matched these trends, despite binding of CDK2 to TL12-186 in all phases. These data indicate that target subpopulation degradation can occur, dictated by the formation of the ternary complex. These studies additionally underscore the importance of profiling degradation compounds in cellular systems where complete pathways are intact and target proteins can be characterized in their relevant complexes.